2017
DOI: 10.3390/diseases5040031
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the Disability of the Arm, Shoulder and Hand Score and Muscle Strength in Post-Cardiac Surgery Patients

Abstract: Background: The Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire is a valid and reliable patient-reported outcome measure. DASH can be assessed by self-reported upper extremity disability and symptoms. We aimed to examine the relationship between the physiological outcome of muscle strength and the DASH score after cardiac surgery. Methods: This cross-sectional study assessed 50 consecutive cardiac patients that were undergoing cardiac surgery. Physiological outcomes of handgrip strength and kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…Upper limb exercise capacity plays an important role in many basic and instrumental activities of daily living and may provide unique information about upper extremity endurance not reflected in the field-based walking tests. Previous studies in similar populations have found an upper limb impairment in patients after breast cancer or cardiac surgery[ 29 ], showing decreased functionality and exercise capacity after surgery, similar to our results. However, and despite its importance, we have not found studies about UL exercise capacity after lung resection.…”
Section: Discussionsupporting
confidence: 92%
“…Upper limb exercise capacity plays an important role in many basic and instrumental activities of daily living and may provide unique information about upper extremity endurance not reflected in the field-based walking tests. Previous studies in similar populations have found an upper limb impairment in patients after breast cancer or cardiac surgery[ 29 ], showing decreased functionality and exercise capacity after surgery, similar to our results. However, and despite its importance, we have not found studies about UL exercise capacity after lung resection.…”
Section: Discussionsupporting
confidence: 92%
“…13 A low but significant correlation (r= −0.32) between grip strength and DASH scores has also been reported for patients examined one month after cardiac surgery. 14 Sunderland et al demonstrated high correlations between grip strength and performance on the Frenchay Arm Test (r= 0.91), Motor Club Assessment (r= 0.86), and Peg Test (r= 0.79) by patients with stroke. 15 Although grip strength is not directly required for the performance of functional activities such as gait, it does distinguish between older adults on the basis of their mobility.…”
Section: Grip Strength As a Biomarker Of Current Statusmentioning
confidence: 98%
“…We previously reported on our cross-sectional investigation on the relationship between handgrip and knee extensor muscle strength and the DASH score of cardiac surgery patients at one month following surgery (74.4% men, age: 62.1 years) [7] and found that both strength factors correlated negatively with the DASH score [7]. In that study, we proposed that the DASH score could be valuable in assessing post-cardiac surgery patients’ handgrip and knee extensor muscle strength as a representative measure of upper and lower extremity function [7].…”
Section: Introductionmentioning
confidence: 99%